Brazilian propolis antileishmanial and immunomodulatory effects - Da Silva, Suelen Santos; Thomé, Graciele Da Silva; Cataneo, Allan Henrique Depieri; Miranda, Milena Menegazzo; Felipe, Ionice; Andrade, Célia Guadalupe Tardeli de Jesus; Watanabe, Maria Angélica Ehara; Piana, Gilce Maria [UNESP]; Sforcin, José Maurício [UNESP]; Pavanelli, Wander Rogério; Conchon-Costa, Ivete (Hindawi, 2013)
The antileishmanial and immunomodulatory effects of propolis collected in Botucatu, São Paulo State, Brazil, were evaluated in Leishmania (Viannia) braziliensis experimental infection. The antileishmanial effect of propolis on promastigote forms was verified by reducing growth and by promoting morphologic alterations observed by scanning electron microscopy. In in vitro immunomodulatory assays, macrophages were pretreated with propolis and then infected with L. (V.) braziliensis. In vivo, supernatants from liver cells and peritoneal exudate of BALB/c mice pretreated with propolis and infected with Leishmania (107/mL promastigotes) were collected, and TNF- α and IL-12 were measured by ELISA. Macrophages incubated with propolis showed a significant increase in interiorization and further killing of parasites. An increased TNF- α production was seen in mice pretreated with propolis, whereas IL-12 was downregulated during the infection. In conclusion, Brazilian propolis showed a direct action on the parasite and displayed immunomodulatory effects on murine macrophages, even though the parasite has been reported to affect the activation pathways of the cell. The observed effects could be associated with the presence of phenolic compounds (flavonoids, aromatic acids, and benzopyranes), di- and triterpenes, and essential oils found in our propolis sample. © 2013 Suelen Santos da Silva et al.
Keywords: antileishmanial agent; immunomodulating agent; interleukin 12; propolis; tumor necrosis factor alpha; animal experiment; animal model; Brazil; controlled study; cytokine production; down regulation; immunomodulation; in vitro study; infectious disease ELISA kit; Leishmania braziliensis; leishmaniasis; macrophage; male; mouse; nonhuman; priority journal; scanning electron microscopy